1990
DOI: 10.1590/s0373-55241990000200003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diel and spatial distribution patterns of ichthyoplankton and ichthyoneuston in the Southeastern Brazilian Bight

Abstract: Fish larvae were collected by neuston and bongo nets, in the Southeastern Brazil, during four océanographie cruises (January 1980; January 1981; October 1981; and March 1982). The results are compared and analyzed in order to study the patterns of diel vertical distributions of fish larvae and to detect sampling problems. Larvae collected with neuston net were quite different in types and size composition, when compared with those collected with bongo net in oblique tows. Clear tendency of stratification in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Many species considered rare in the present study were very abundant in the subsurface water in Campos Basin (Bonecker et al, ) and in deeper waters in other areas of the Brazilian coast (Goçalo, Katsuragawa, & Silveira, ; Namiki et al, ). Therefore, the low frequency and abundance of some species in the present study probably reflect net avoidance of fish larvae during the day, due to the visual and swimming capacity of larger larvae (Doyle, ; Katsuragawa & Matsuura, ), or because they are pseudoneuston species, which means that their center of distribution occurs at deeper layers and the surface is the edge of their vertical range of distribution (Hempel & Weikert, ). Besides, many species belong to the facultative neuston and undergo vertical migration, aggregating near the surface only during the night, e.g., T. lathami , Myctophidae species (Doyle, ; Hempel & Weikert, ), and some physostomous fishes (e.g., Engraulidae species) that migrate to the surface, where they inhale air through their widely opened mouth, to inflate their gas bladder and may reduce sink rate (Landaeta & Castro, ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Many species considered rare in the present study were very abundant in the subsurface water in Campos Basin (Bonecker et al, ) and in deeper waters in other areas of the Brazilian coast (Goçalo, Katsuragawa, & Silveira, ; Namiki et al, ). Therefore, the low frequency and abundance of some species in the present study probably reflect net avoidance of fish larvae during the day, due to the visual and swimming capacity of larger larvae (Doyle, ; Katsuragawa & Matsuura, ), or because they are pseudoneuston species, which means that their center of distribution occurs at deeper layers and the surface is the edge of their vertical range of distribution (Hempel & Weikert, ). Besides, many species belong to the facultative neuston and undergo vertical migration, aggregating near the surface only during the night, e.g., T. lathami , Myctophidae species (Doyle, ; Hempel & Weikert, ), and some physostomous fishes (e.g., Engraulidae species) that migrate to the surface, where they inhale air through their widely opened mouth, to inflate their gas bladder and may reduce sink rate (Landaeta & Castro, ).…”
Section: Discussionmentioning
confidence: 91%
“…Euneuston species were represented by larvae of Mullidae, Exocoetidae, O. similis, Belonidae, Coryphaenidae, Selar crumenophthalmus (Bloch, 1793), and Kyphosus incisor (Cuvier, 1831). These species was classified as euneuston according to other authors (Hempel & Weikert, ; Katsuragawa & Matsuura, ; Vilchis, Balance, & Watson, ). Bonecker et al () also found Exocoetus obtusirostris Günther, 1866 and Coryphaena equiselis Linnaeus, 1758 near the surface during the day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the ichthyoplankton of the Campos Basin have been conducted since the 1980s and have focused on describing the distribution patterns of species of interest to fisheries (Dos‐Santos et al, 2019; Matsuura, 1982) or those species that are abundant in oceanic waters (Namiki et al, 2017) and characterizing the distribution of larval assemblages along a vertical gradient (Bonecker et al, 2012; Katsuragawa & Matsuura, 1990). However, horizontal (spatial) gradients of ichthyoplankton have not been studied in the Campos Basin.…”
Section: Introductionmentioning
confidence: 99%